DYNAMICS OF SHORT-RUN AND LONG-RUN INTERACTIONS AMONG GOLD AND MACRO ECONOMIC VARIABLES: AN ARDL APPLICATION IN INDIA - Mrs. RitimaKhindri, Dr. Ashish Arora (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
As per “Law of Demand”, The prices of the gold as a commodity are determined by its demand and supply. The demand for the gold is driven by jewellery, industrial and investment demand. The supply of the gold constitute newly-mined gold, net mobilization of Central Banks reserves and the recycled gold. But, Demand plays pivotal role in its price formation rather than supply that is restricted. A major part is played by investment demand for the gold by the investors in its price formations. Indeed, Investment demand for gold is more associated with the fluctuations in exchange rates, crude oil prices, stock market indices and interest rates, that motivate an investor to make an investment in gold as an important hedging tool. This enhance investors appetite for capital preservation and wealth accumulation motives. To estimate short-run and long-run relationship among these variablesfrom 1st April 2005 till 31st March 2019 in India, An ARDL (Auto Regressive Distributed Lag) bound testing model has been used, by undertaking interest rates (MIBOR rates) as the important variable impacting gold prices along with US Dollar, crude oil prices and stock market prices. Results reveal that MIBOR rates tend to have long-run relationship with Gold, USD, Crude oil and Nifty. However for the short run, US Dollar, Stock market movements and Crude oil are the major determinants of Gold prices.